Patients Unmet Needs in Chronic Rhinosinusitis With Nasal Polyps Care: A Patient Advisory Board Statement of EUFOREA - Claeys, N.; Teeling, M. T.; Legrand, P.; Poppe, M.; Verschueren, P.; De Prins, L.; Cools, L.; Cypers, L.; Fokkens, W. J.; Hopkins, C.; Hellings, P. W. (Frontiers in Allergy, 2021)
Background: European patients with chronic rhinosinusitis with nasal polyps (CRSwNP) have had only limited occasions to unite to have their voices heard, hence missing the opportunity to contribute to the improvement of CRSwNP care. Aims: To identify unmet needs in CRSwNP from the perspective of CRSwNP patients from the Patient Advisory Board (PAB) of the European Forum for Research and Education in Allergy and Airways diseases (EUFOREA). Methodology: Semi-structured interviews were conducted individually with 15 European patients with CRSwNP and with a disease history of more than 2 years. Patients shared their burden of the disease and frustrations related to CRSwNP care, experiences with key pillars of current treatment options, shortcomings of the current care pathways and recommendations for improvement of care. A panel of 30 members of the Patient Advisory Board reviewed the interview report and provided further input during 2 virtual meetings. Results: CRSwNP patients indicated the need for greater awareness from society and physicians of the disease burden with impact on social function and wellbeing. Along with a loss of ability to smell and the continuous presence of secretions in the nose, most patients reported poor sleep quality and psychological impact as the most bothersome symptoms. Patients’ frustrations relate primarily to the underestimation of the disease burden, the lack of coordination of care and the limited treatment options available to them. Treatment options with oral corticosteroids and/or sinus surgery both have positive and negative aspects, including the lack of long-lasting efficacy. Better coordination of care, more patient-centered care, greater public awareness, increases in research on the disease mechanisms and better therapeutic options would be warmly welcomed by CRSwNP patients. Conclusions: This statement of the EUFOREA Patient Advisory Board on CRSwNP provides novel insights on the underestimation of the burden of CRSwNP and shortcomings of current care. Multiple recommendations made by the patients can underpin action plans for implementation of better care for CRSwNP among all physicians treating patients with this disabling disease.